Psychological Impact of COVID-19 Pandemic on Health Care Workers: A Cross Sectional Study - Zaina Jabeen; Aysha Rani; Sohaib Ahmed; Sadaf Ghaffar; Tazaeen Hina Kazmi; Wasim-ud-Din (BioMedica, 2020)
Background and Objective: The Coronavirus disease 2019 (COVID-19) pandemic has affected more than four million people in 213 countries. Health care workers (HCWs) who deal with COVID-19 patients have a high chance of getting infected. They have got valid concerns regarding their own health as well as the impact it can have on the wellbeing of their family and acquaintances. The current study aims to assess the prevalence of psychological problems among HCWs during the COVID-19 pandemic. Methods: A cross-sectional study was conducted among HCWs of Wah Medical College and Pakistan Ordnance Factories (POF) Hospital Wah Cantt from 1st May 2020 to 7th May 2020 after an ethical approval by ethical review board. A total of 340 HCWs participated by filling an online questionairre; questions on demographic profile and validated Depression, Anxiety and Stress Scale–21 (DASS-21) score were included. Frequency of depression, anxiety and stress and mean DASS-21 scores between house officers and all other healthcare workers and between Medicine and allied department and other departments was assessed. Data was analysed using Statistical Package for the Social Sciences (SPSS)-23. P-value ≤ 0.05 was considered statistically significant. Results: Among 340 HCWs majority i.e. 66.8% were less than 35 years of age and the mean age of participants was 40.65 ± 11.64 years. There was a female proponderance with a F:M ratio of 1.7:1. Most (55.3%) of the participants were single and there was a high percentage of house officers with 45% among all. The overall prevalence of depressiom, anxiety and stress among all HCWs was 32.9%, 25% and 23.5% respectively. The depression, anxiety and stress among house officers than other HCWs and higher prevalence in Medicine and Allied Departments than other departments. Conclusion: As the global threat of COVID-19 continues to emerge, it is important not to underestimate the psychological impact of this pandemic on HCWs. Interventions and support to especially vulnerable groups of HCWs will help improve psychological health, which in turn will help improve the quality of patient care.